Inx-in(x+3)=6

Simple and best practice solution for Inx-in(x+3)=6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for Inx-in(x+3)=6 equation:


Simplifying
Inx + -1in(x + 3) = 6

Reorder the terms:
nxI + -1in(3 + x) = 6
nxI + (3 * -1in + x * -1in) = 6
nxI + (-3in + -1inx) = 6

Reorder the terms:
-3in + -1inx + nxI = 6

Solving
-3in + -1inx + nxI = 6

Solving for variable 'i'.

Move all terms containing i to the left, all other terms to the right.

Add '-1nxI' to each side of the equation.
-3in + -1inx + nxI + -1nxI = 6 + -1nxI

Combine like terms: nxI + -1nxI = 0
-3in + -1inx + 0 = 6 + -1nxI
-3in + -1inx = 6 + -1nxI

Reorder the terms:
-6 + -3in + -1inx + nxI = 6 + -1nxI + -6 + nxI

Reorder the terms:
-6 + -3in + -1inx + nxI = 6 + -6 + -1nxI + nxI

Combine like terms: 6 + -6 = 0
-6 + -3in + -1inx + nxI = 0 + -1nxI + nxI
-6 + -3in + -1inx + nxI = -1nxI + nxI

Combine like terms: -1nxI + nxI = 0
-6 + -3in + -1inx + nxI = 0

The solution to this equation could not be determined.

See similar equations:

| Y/3-y=4 | | 6(2x+4)=8x-3 | | r=6(2r+1) | | -2(3x-1)-4x=5x-(3x-6) | | -12n-(4n+5)=16-3n | | -10-bracket(-7)+2= | | 1/6×5= | | 3/2=3x-4/7 | | -8-(8)= | | 1/6×5 | | y-4x+110=0 | | x^2-9x+y^2=0 | | 7x^2-448= | | r=3(r+.5) | | 11/3×4/9 | | 6-9-(-6)= | | x-2y+74=0 | | 4/9×n=11/3 | | .8=.2+x-0.15 | | 3/100=n/660 | | x+5(x-5)=11 | | 3g+2g+5=0 | | Q^2+16q-15=0 | | 2(3+q)+q=3 | | 4-10-4-(-3)+3= | | an=1+(-1)n | | =2b*a | | 6(r+0.5)=r | | =2axb | | 5z+3=8z-4z | | h=-16t^2+132t+5 | | 0=32t^2+12t |

Equations solver categories